2017
DOI: 10.1016/j.rmed.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Real-life effectiveness of asthma treatment with a fixed-dose fluticasone/formoterol pressurised metered-dose inhaler – Results from a non-interventional study

Abstract: In this one-year study, FP/FORM treatment was associated with clinically relevant improvements in asthma status in a diverse population of patients under real-life conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
5
15
1
Order By: Relevance
“…Stratification by the FDC ICS/LABA type showed that, despite the much lower sample size, switching from DPI to FP/FORM pMDI was still associated with significantly better asthma control. Previous studies have reported FP/FORM to be efficacious in improving asthma control and decreasing asthma exacerbations in clinical trial settings as well as in a prospective non‐interventional post‐authorization safety study setting . This study supports the effectiveness of FP/FORM pMDI in the context of real‐world setting.…”
Section: Discussionsupporting
confidence: 81%
“…Stratification by the FDC ICS/LABA type showed that, despite the much lower sample size, switching from DPI to FP/FORM pMDI was still associated with significantly better asthma control. Previous studies have reported FP/FORM to be efficacious in improving asthma control and decreasing asthma exacerbations in clinical trial settings as well as in a prospective non‐interventional post‐authorization safety study setting . This study supports the effectiveness of FP/FORM pMDI in the context of real‐world setting.…”
Section: Discussionsupporting
confidence: 81%
“… 9 Dysphonia was also the most common treatment-related AE in the ffAiRNeSS study. 28 The rates of bronchopneumonia and oropharyngeal candidiasis were low (0.1% in both cases).…”
Section: Discussionmentioning
confidence: 81%
“…Together with a 12-month non-interventional study of fluticasone/formoterol conducted in Germany (ffAiRNeSS), 28 the PASS reported here was conducted as part of an agreed EU RMP. The current study was designed with the primary objective of collecting safety information during routine clinical use of fluticasone/formoterol, and also monitored the effectiveness of this ICS/LABA in achieving asthma control in real-world practice across eight European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, long-term data from two clinical studies have demonstrated good efficacy, safety, and tolerability with this ICS/LABA combination, including a low rate of exacerbations, over study periods of up to 60 weeks [33,35]. Real-world data from non-interventional studies in over 4000 patients with asthma support the effectiveness and safety/ tolerability of FP/FORM pMDIs in general clinical practice [29,37]. In addition, real-world data from a randomized pragmatic trial demonstrated that asthma control was maintained when the FP/ FORM pMDI dose was stepped down from high to medium [36].…”
Section: Fp/form Clinical Datamentioning
confidence: 89%
“…An extensive clinical dataset exists for FP/FORM administered via a pMDI (Table 2) [29][30][31][32][33][34][35][36][37][38]. Furthermore, long-term data from two clinical studies have demonstrated good efficacy, safety, and tolerability with this ICS/LABA combination, including a low rate of exacerbations, over study periods of up to 60 weeks [33,35].…”
Section: Fp/form Clinical Datamentioning
confidence: 99%